The Principle of the State's Right to Control Land on the Establishment of a Land Bank in Indonesia's Perspective of Agrarian Reform - Suyanto Suyanto; Umi Khulsum (Faculty of Law, Universitas Jenderal Soedirman, 2022)
The establishment of a land bank related to problems in land acquisition today has resulted in a shift in the view of land as a commodity that is considered strategic. This triggered land liberalization, which resulted in land prices soaring due to the games of land speculators so that land compensation issues constrained the projects planned by the government in building infrastructure. The problem is the influence of the principle of the right to control the state in the formation of a land bank and how is the position of the land bank in the perspective of agrarian reform. The research method used is normative juridical in the form of legal behaviour by reviewing statutory regulations. Land rights are derived from the state's right to control, which can be given to the community individually or in the form of a legal entity or jointly. State rights in the land sector are rights granted to the state to regulate and organize the allocation, use, supply, and maintenance in the land sector; regulate the land bank whether it is by what the government intended or return to the old guidelines, namely domein verklaring. Therefore, as the legislator and implementer, the government is expected to revise the Basic Agrarian Law. The revision prevents the right to control land, which is feared to happen again, like in the Dutch colonial era. The Basic Agrarian Law is considered too outdated and does not follow current land problems. Keywords: The right to control the state; land bank; domein verklaring; land acquisition